Dilemmas Between Popular Election and International Human Rights Obligations in the New 2024 Judicial Reform - Zenteno Trejo, Blanca Yaquelin (2025)
This article analyzes the implications of the recent judicial reform in Mexico, which introduces the popular election of judges, from the perspective of the State’s international human rights obligations. The reform significantly modifies the structure and functioning of the Federal Judiciary (PJF), as it establishes that all its members—including the Justices of the Supreme Court of Justice of the Nation (SCJN), the magistrates of the Electoral Tribunal, the members of the Judicial Discipline Tribunal, circuit magistrates, and district judges—will be elected by popular vote for fixed terms and, in some cases, with the possibility of reelection. The reform raises concerns regarding compliance with international standards on judicial independence and impartiality: the introduction of “faceless judges” runs counter to the jurisprudence of the Inter-American Court of Human Rights, which considers this figure a violation of due process; the mechanism of popular election may not adequately guarantee the integrity, suitability, and proper legal training required for judicial appointments under international principles; the early termination of the terms of current judges affects stability and security of tenure; the absence of clear regulations on campaign financing opens the door to undue external pressures and influences; the uniform application of the reform to state judiciaries points to increasing centralization; and the convergence of judicial and political electoral processes raises questions about the politicization of judicial offices. In conclusion, while the reform seeks to address structural deficiencies in the administration of justice, several of its elements may be at odds with Mexico’s international human rights commitments, weakening rather than strengthening the Judiciary.